Relationship between civic engagement and level of people's participation in local government - Mohammadi, Seyed Hamid; Syed Abdul Rashid, Sharifah Norazizan; Emby, Zahid (Marsland Press, 2011)
This paper attempts to identify the relationship between civic engagements of local people and level of their participation in local government of Torbat-Heydarieh, Iran. The paper is based on the study carried out among 400 citizens of Torbat-Heydarieh. The analysis of data uses Pearson correlation to determine the relationship between variables involved. The findings reveal that two levels of participation (tokenism and citizen-power) have positive and significant relationship with civic engagement, while there is no significant relationship between non-participation level and civic engagement. The findings of the study imply that those respondents who engage more in civic activities would participate in high level of participation in local government.